Inappropriate left ventricular mass and poor outcomes in patients with angina pectoris and normal ejection fraction. Issue 2 (March 2015) - Huang, Bao-Tao; Peng, Yong; Liu, Wei; Zhang, Chen; Huang, Fang-Yang; Wang, Peng-Ju; Zuo, Zhi-Liang; Liao, Yan-Biao; Chai, Hua; Li, Qiao; Zhao, Zhen-Gang; Luo, Xiao-Lin; et al.
<x xml:space="preserve">Abstract</x> Objectives Although inappropriate left ventricular mass has been associated with clustered cardiac geometric and functional abnormalities, its predictive value in patients with coronary artery disease is still unknown. This study examined the association of inappropriate left ventricular mass with clinical outcomes in patients with angina pectoris and normal ejection fraction. Participants and methods Consecutive patients diagnosed with angina pectoris whose ejection fraction was normal were recruited from 2008 to 2012. Inappropriate left ventricular mass was determined when the ratio of actual left ventricular mass to the predicted one exceeded 150%. The primary endpoint was a composite of all-cause death, nonfatal myocardial infarction, and nonfatal stroke. Clinical outcomes between the inappropriate and appropriate left ventricular mass group were compared before and after propensity matching. Results Of the total of 1515 participants, 18.3% had inappropriate left ventricular mass. Patients with inappropriate left ventricular mass had a higher composite event rate compared with those with appropriate left ventricular mass (11.2 vs. 6.6%, P=0.010). Multivariate Cox regression analyses showed that inappropriate left ventricular mass was an independent risk factor for adverse events (adjusted hazard ratio, 1.59; 95% confidence interval, 1.03–2.45; P=0.035). The worse outcome in patients with inappropriate left ventricular mass was further validated in a propensity matching cohort and patients with the traditional definition of left ventricular hypertrophy. Conclusion Inappropriate left ventricular mass was associated with an increased risk of adverse events in patients with angina pectoris and normal ejection fraction.